Titanium-Dioxide-Coated Silica Microspheres for High-Efficiency Dye-Sensitized Solar Cell - Devender; Dangi A. (My University, 2025)
In order to improve the efficiency of a dye-sensitized solar cell (DSSC) by using silica microspheres coated with titanium dioxide (TiO2), silica microspheres were prepared by the sol-gel method using tetraethyl orthosilicate as the starting material and hydrochloric acid to catalyze the reaction. Silica microspheres thus formed were coated with TiO2. The presence of TiO2 improved the photocatalytic properties of silica, which is responsible for a significant increase in the decomposition of the dye molecules. Enhancement of this decomposition was ascertained by measuring the difference in initial and final concentrations of dye in a solution containing the coated microspheres and the die. The use of the microspheres can boost the efficiency of DSSCs. © 2011 The American Ceramic Society.